DETECTION OF GM SOYA AND CORN IN SOME OF THEIR FOOD PRODUCTS IN SULEIMANIA/KURDISTAN REGION OF IRAQ - Hama Karim, Tazhan; Hassan, Khulod (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate Genetically Modified (GM) Soybean and corn, in some foodstuffs, using molecular screening method based on Polymerase chain Reaction (PCR). To achieve that, a total of 60 food product samples containing corn and soy bean were collected from markets of Suleimania /Iraq. PCR was first applied to detect the presence of soybeans and corn using species specific primers. For the general screening of the GM foods, primers targeting the genetic elements that located in the majority of transgenic crops were used, which named NOS terminator and CaMV 35S promoter. Then primers targets specific events in these crops were used, which are GTS 40-3-2, or (RRS) and B t11 in soybeans and corn respectively. The results of this study showed the presence of genes representing soybeans and corn in all foods containing them. General screening of food samples also showed that the incidence of GMOs in the studied samples were 75 % and 82% for P35S and t NOS respectively. Regarding to the events specific, the Bt-11 gene detected in about 34% of food samples contain corn and GTS 40-3-2gene detected in 70 % of food samples contain soya.